Biology and Morphometrics of Pulse Beetle, Callosobruchus chinensis L. on Chickpea - Mishra, Om Prakash; Singh, Kh. Ibohal; Haldhar, S. M.; Sinha, Bireswar; Singh, N. Okendro; Chiranjiv,; Roy, Pranita; Ibrar, S. M. (International Journal of Economic Plants, 2023)
A study was conducted during year 2022–23 for a period of six months for several generations in controlled laboratory environment at the College of Agriculture, Iroisemba, Imphal, Manipur India on the biology and morphometrics of the pulse beetle, Callosobruchus chinensis, on GNG 2207 chickpea cultivar. The experiments were conducted within a BOD incubator, maintaining a constant temperature of 30±1ºC and relative humidity ranging from 70±1 %. Life cycle of C. chinensis encompassed four distinct stages: egg, grub, pupa, and adult. The collected data unveiled essential insights such as the egg incubation period spanned 5–8 days, while grub stage consisted of four instars, taking 16–21 days for complete development. Pupation occurred over a period of 8–9 days. Female adult displayed a longevity range of 8–10 days. In terms of morphometric measurements, the average dimensions for eggs were found to be 0.60±0.05mm in length and 0.35±0.02mm in breadth. The respective lengths and breadths (mm) for the four grub instars, G1, G2, G3, and G4, were as follows: 0.55±0.05 and 0.30±0.02, 1.56±0.09 and 0.91±0.06, 2.68±0.07 and 1.45±0.08, 3.62±0.16 and 1.93±0.08. Pupa measurements yielded an average length and breadth of 3.76±0.22 mm and 2.21±0.05 mm, respectively. Moreover, the dimensions (mm) of adult male and female bruchids were found to be 3.88±0.07, 2.31±0.07, and 4.19±0.10, 2.12±0.11, respectively. The comprehensive life cycle of C. chinensis spanned from 38 to 42 days, encapsulating the various developmental stages.